Application of the Problem-Based Learning Model to Improve Students' Ablution Skills in Islamic Education Learning for Students at SD Negeri 105447 Nagori - Sinaga, Syamanidar; Muis, Mul; Lismayuni (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This research aims to improve students' ablution skills in Islamic education using problem based learning. This research is classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research were elementary school students. This research data was obtained using test and observation techniques. Tests are used to improve students' ablution skills and observations are used to analyze teacher and student learning activities. The data analysis technique used in this research is descriptive statistics by comparing the results obtained with indicators of research success. The results of the research show that learning using problem based learning can improve students' ablution skills. This can be seen from the increase in the percentage of completeness. The increase in student learning outcomes in each cycle with details in the pre-cycle was 47.64%, the first cycle was 78.57% and in the second cycle it increased to 88.57%. Thus, learning using the application of problem based learning can be used as an alternative to improve ablution skills.